2016
DOI: 10.1080/00325899.2016.1169362
|View full text |Cite
|
Sign up to set email alerts
|

Study on microstructure and mechanical properties of spark plasma sintered Alumix 431 powder

Abstract: Spark plasma sintering (SPS) has been used to successfully densify a 7075 aluminium alloy obtained from Alumix 431 powder. Sintering experiments were conducted at the temperature of 450 and 500°C for 2.5, 5 and 10 min. All the presented results confirm the excellent sinterability of Alumix 431 powder in vacuum during the SPS process and clearly show the effect of sintering temperatures and holding times on the densification, microstructure and mechanical properties of the obtained sintered compacts. The best r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Alumix 431 (ECKA Granules Germany GmbH, Velden, Germany) powder, without lubricant, exhibiting the chemical composition shown in Table 1, was spark plasma sintered using an HP D 25/3 furnace (FCT Systeme GmbH, Rauenstein, Germany), similar to the procedure described by the authors in [15]. The SPS parameters were chosen on the basis of the experimental results described in [5]. The powder was heated up to 500 • C at 100 • C/min in vacuum and held at the sintering temperature for 5 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alumix 431 (ECKA Granules Germany GmbH, Velden, Germany) powder, without lubricant, exhibiting the chemical composition shown in Table 1, was spark plasma sintered using an HP D 25/3 furnace (FCT Systeme GmbH, Rauenstein, Germany), similar to the procedure described by the authors in [15]. The SPS parameters were chosen on the basis of the experimental results described in [5]. The powder was heated up to 500 • C at 100 • C/min in vacuum and held at the sintering temperature for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Representative LM and SEM micrographs of the SPSed specimens are presented in Figure 1. The SEM micrograph of the unetched microstructure (Figure 1b) clearly shows Al grains of different sizes (dark contrast phase) with grain boundaries containing intermetallic phases (light contrast phase) similar to [3,5]. The microstructure is heterogeneous because of the simultaneous presence of very large and fine grains.…”
Section: Microstructurementioning
confidence: 99%
See 1 more Smart Citation
“…This is accomplished by contributing to the rupture of the oxide layer at the surface of the pure aluminum powder, which has been demonstrated in previous studies [10][11][12][13][14][15][16][17]. However, it has been shown by Garbiec and Siwak [18] and Rudinsky et al [19] that Alumix 431 powder sintered by SPS exhibits low ductility during tensile or bending tests due to the lack of bonding between particles. It has been suggested that the formation of the spinel layer arising from the reaction of Mg and the alumina layer would impose the requirement for a higher applied load to break the oxide layer [20].…”
Section: Introductionmentioning
confidence: 85%
“…The studies have shown that incremental changes in SPS time generally enhances the densification of metals and alloys due to enhanced mass transfer [36], improved inter-particle bonding, reduced porosities [18], and enhanced heat flux [37], as depicted in Fig. 4, for Aluminum [35], and stainless steel 430L [19] as examples.…”
Section: Sps Timementioning
confidence: 99%